Resistance behavior of hybrid clones of cluster onion (Allium cepa) against anthracnose disease caused by Colletotrichum gloesphorioides - Sritharan, S.; Kirunsiga, U.J.; Arasakesary, S.J. (Faculty of Animal Science and Export Agriculture, Uva Wellassa University of Sri Lanka, Badulla, Sri Lanka, 2026)
Red onion (Allium cepa) is an important cash crop cultivated in Sri Lanka. Onion Anthracnose caused by Colletotrichum gloeosporioides, is a major disease affecting onion production in dry zone of Sri Lanka. When environmental conditions are conducive, it spreads rapidly and affects the entire field especially after rainy season. Management of this disease is very difficult because this fungus can survive in crop residues and plant debris. Screening of fifth generation hybrid clones of cluster onion (Allium cepa) for resistance behavior against anthracnose disease is essential to the farmers to reduce the pesticide usages and yield losses. The development of advanced hybrid clones, such as fifth-generation hybrids, is a crucial step in stabilizing these traits and ensuring consistent performance under field conditions. This study aims to evaluate the resistance behavior of fifth-generation hybrid clones of red onion against anthracnose disease caused by Colletotrichum gloeosporioides.44 hybrid clones were selected and they were used as treatments. Two experiments were conducted. Growth parameters were taken in Experiment1. Disease incidence and disease severity Index were in taken in Experiment 2.CRD (Complete randomized design) for pot experiment 2 and RCBD (Randomized complete block design) for field experiment 1 were used to perform analysis of variance (ANOVA) and tukey mean separation was administered to identify best treatment at p<0.05 using SAS 9.1. According to the results, the resistant hybrid clone was identified as the cross MICLO1×MH4 (E19), while moderately resistant hybrid clones were the crosses TVM6×MICLO4 (E32), Vethalam (E44), MH4×TVM6 (E21), TVM6×MICLO4 (E31), and TVM6 (E43). Bulb yield was also significantly reduced due to anthracnose in onion. Therefore, the hybrid clones E19, E32, E44, E21, E31, and E43 (TVM6) were selected as promising based on disease tolerance capacity. These lines could be used for crop improvement programs or promoted for future variety release.
Keywords: Advanced hybrid clones; Colletotrichum gloesporioides; Onion anthracnose; Red onion; Resistance